Interprosthetic femoral fractures managed with modern distal femoral locking plates: 10 years' experience at a UK major trauma centre. Issue 7 (July 2021) - Mittal, Aaina; Poole, William; Crone, David
Highlights: Incidence of interprosthetic femoral fractures (IFFs) is increasing with an ageing population and operative management can be challenging. In this case series, 49 IFFs were managed with distal femoral locking plates, using minimally invasive plate osteosynthesis (MIPO) techniques. Adopting fixation with a bridging construct allowed for early weight bearing with high rates of union observed. When non-union occurred, early failure of fixation was observed in all of these cases, requiring revision surgery. Abstract: Introduction: Interprosthetic femoral fractures (IFF) are rare but increasing with an ageing population. Operative management is challenging and there is currently a paucity of outcome data in literature. The purpose of this study was to evaluate outcomes of IFFs managed with modern distal femoral locking plates, in a larger sample size than previously published. Method: This retrospective study reviewed 49 closed IFFs in 48 patients at a major trauma center from 2009 to 2019 occurring between previous total hip arthroplasty (n=38), hemi hip arthroplasty (n=3), dynamic hip screw (n=6) or cephalomedullary nail (n=2) and total knee arthroplasty. They were managed with Minimally Invasive Plate Osteosynthesis (MIPO) employing modern biological fixation techniques and stabilised with VA-LCP Condylar (Synthes; n=28) or Peri-Loc (S&N; n=21) plate. Clinical and radiographic outcomes were measured. Results: The majority of fractures were in female patients (80%), who were elderly (average 83 years), and comorbid (55% ASA grade 3 or 4). Most fractures were Pires type IIA and OTA/AO type 33A. Average plate spanning femur was 16 holes, with average working length of 6 holes. 86% had unrestricted weight bearing immediately post operatively. 31 fractures reached radiological (n=25) or clinical (n=6) union. 13 patients died with 2 lost to follow up. There were 3 non-unions, with implant failure occurring before 4 months in all 3. We present a union rate of 91% (n=31/34). Conclusion: IFFs are occurring with increasing frequency in a frail elderly population. In patients with IFFs, MIPO and biological fixation techniques using modern distal femoral locking plates can achieve high rate of union when combined with immediate unrestricted weight bearing postoperatively.